2012
DOI: 10.1158/2159-8290.cd-11-0170
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic Complexity and AKT Dependence in Serous Ovarian Cancer

Abstract: Effective oncoprotein-targeted therapies have not yet been developed for ovarian cancer. To explore the role of PI3 kinase/AKT signaling in this disease, we performed a genetic and functional analysis of ovarian cancer cell lines and tumors. PI3K pathway alterations were common in both, but the spectrum of mutational changes differed. Genetic activation of the pathway was necessary, but not sufficient, to confer sensitivity to selective inhibition of AKT and cells with RAS pathway alterations or RB1 loss were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
99
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 48 publications
5
99
0
Order By: Relevance
“…Several studies have addressed PI3K/AKT pathway inhibition in ovarian cancer. In one study, a subset of ovarian cancer cell lines was sensitive to inhibition of AKT1 and AKT2, whereas those expressing AKT3 required inhibition of all three isoforms (28). In a separate study, modest clinical responses were seen in a phase-I trial incorporating mTOR inhibitors in the patients with PIK3CA mutant compared with PIK3CA wild-type cancers (36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have addressed PI3K/AKT pathway inhibition in ovarian cancer. In one study, a subset of ovarian cancer cell lines was sensitive to inhibition of AKT1 and AKT2, whereas those expressing AKT3 required inhibition of all three isoforms (28). In a separate study, modest clinical responses were seen in a phase-I trial incorporating mTOR inhibitors in the patients with PIK3CA mutant compared with PIK3CA wild-type cancers (36).…”
Section: Discussionmentioning
confidence: 99%
“…Hanrahan et al (28) recently reported a substantial number of PI3K pathway alterations in ovarian cancer. We extended this analysis by analyzing a substantially larger number the number of samples and also incorporating GAB2 in our analysis.…”
Section: Gab2 Transforms Immortalized Ovarian and Fallopian Tube-derivedmentioning
confidence: 99%
See 1 more Smart Citation
“…Dual inhibition of PI3K/Akt/mTOR signalling with a combination of pictilisib and pitavastatin increased apoptosis in Ovcar-3 cells, whilst demonstrating antagonism in A2780 and Igrov-1 cells. Ovcar-3, Ovcar-8, Igrov-1 and A2780 cells have PI3K/Akt pathway alterations consistent with activation of PI3K/Akt signalling, suggesting that these cell lines may be particularly sensitive to PI3K pathway inhibition (23,24). This was supported by the submicromolar IC 50 values obtained for pictilisib in all cell lines tested.…”
Section: Discussionmentioning
confidence: 61%
“…This was supported by the submicromolar IC 50 values obtained for pictilisib in all cell lines tested. The lack of synergy between pitavastatin and pictisilib in A2780 and Igrov-1 cells may be due to PTEN deletions in these cell lines, resulting in low or undetectable levels of PTEN protein (23). This may hyperactivate the Akt The number of dead Ovcar-3 and Igrov-1 cells was determined by trypan blue staining following exposure for 72 h to either solvent (DMSO), or 12 and 6 µM pitavastatin, and 1 and 0.6 µM ABT-737, 2 and 3 µM obatoclax, or 2 and 0.7 µM pictilisib.…”
Section: Discussionmentioning
confidence: 99%